Association of remnant cholesterol with renal function and its progression in patients with type 2 diabetes related chronic kidney disease - Li, Qiuhong; Wang, Tongdan; Shao, Xian; Fan, Xiaoguang; Lin, Yao; Cui, Zhuang; Liu, Hongyan; Zhou, Saijun; Yu, Pei (Frontiers in Endocrinology, 2024)
The association of Remnant cholesterol (RC) with renal function and its progression in patients with Type 2 diabetes (T2DM) related chronic kidney disease (CKD) remains unclear.Methods: 8,678 patients with T2DM-related CKD were included in cross-sectional analysis, and 6,165 patients were enrolled in longitudinal analysis and followed up for a median of 36.0 months. The outcomes were renal composite endpoint event and rapid progression of renal function.Results: 24.54% developed a renal composite endpoint event, and 27.64% rapid progression of renal function. RC levels above 0.56 mmol/L independently increased the risk of both renal composite endpoint (HR, 1.17; 95% CIs, 1.03-1.33) and rapid progression of renal function (OR, 1.17; 95% CIs, 1.01-1.37).TG levels above 1.65 mmol/L only increased the risk of renal composite endpoint (HR, 1.16; 95% CIs, 1.02 -1.32). TC levels above 5.21 mmol/L increased the risk of renal composite endpoint (HR, 1.14; 95% CIs, 1.01-1.29) only in patients with proteinuria≥0.5g/d. Conversely, HDL-C levels below 1.20 mmol/L or above 1.84 mmol/L increased the risk of rapid progression of renal function (OR, 0.88; 95% CIs, in patients with proteinuria<0.5g/d (all P<0.05).In patients with T2DM-related CKD, RC was an independent risk factor for progression of renal function, and maintaining it below 0.56 mmol/L could reduce the risk of renal function progression